Análise dos editoriais de veja no período pré/pós-eleição presidencial: uma reflexão sobre o discurso que estrutura o cenário político-social - Schoroder, Luciane Thomé (2006)
This inquiry has as its analysis data corpus a set of Veja magazine editorials which were published before and after the presidential election occurred in 2002, in Brazil. The set of editorials previous to the event is destined to verify what would be the magazine position about the event, trying to comprove whether this media is exemplo how it is affirmed in communication means or it has an ideological position which means not be only informative. Otherwise, the analysis of editorials occurred after to the elections searches to verify another spread out speech which asserts that the press would be opportunist, lining up itself with the power to get benefits of these negotiations revenues. The reflection is conducted considering a hypothesis that any statement based in common sense is supported. Parallel, it is also searched to show as Veja (and communication means in general) constitutes for itself a positive autorepresentation to guarantee a sustentation for the speech that it produces. The utilized theoretical basement is constituted from the Discourse Analysis of the French line having as central authors of support Pêcheux (1995), Charaudeau and Maingueneau (2004), Orlandi (2001 a e b) and Maingueneau (2005). The concepts of this theory which were crucial for this work accomplishment are ethos, inter-discourse, discursive formation and ideology. The used methodology is related to the analytical-interpretative procedures and it operates with removed clippings of the mentioned editorials.